2018
DOI: 10.4103/1735-5362.228941
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic effects of Lippia citriodora in a mouce model of anxiety

Abstract: Lippia citriodora is commonly used in Iranian folk medicine for treatment of many disorders. Since there scientific data to prove the anxiolytic properties of this plant in Iran are scarce, we aimed to evaluate the sedative and anxiolytic activity of the leaf extract and essence of L. citriodora in an animal model of anxiety. The extract and the essence used were obtained after maceration and hydro-distillation of the leaves of L. citriodora, respectively. We evaluated the anti-anxiety profile and sedative act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Bonyani A. and colleagues evaluated the leaf extract essence of LV on mouse models in terms of its sedative and anxiolytic activity. They concluded that the essence of the leaf acts as an antianxiety agent like diazepam through the GABAergic system without any significant reduction of locomotor activity 34 . The results were the same as ours with the exception that we performed the study on humans instead of mice.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Bonyani A. and colleagues evaluated the leaf extract essence of LV on mouse models in terms of its sedative and anxiolytic activity. They concluded that the essence of the leaf acts as an antianxiety agent like diazepam through the GABAergic system without any significant reduction of locomotor activity 34 . The results were the same as ours with the exception that we performed the study on humans instead of mice.…”
Section: Discussionsupporting
confidence: 80%
“…The latest trials have focused on the antianxiety effects of an edible extract of LV in animal models. 34 The results of an animal model study conducted by Razavi et al has demonstrated that intraperitoneal ethanolic and aqueous extracts of LV leaves have antianxiety effects which are probably due to the interaction between GABA receptors and LV ingredients. 35 We obtained similar results in our study but with a difference in the method of usage in which we used the fragrance type of LV instead of the intraperitoneal method.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to characterize the antidepressant effect, six authors resorted to forced swimming tests (Divyajyothi et al, 2015; Emon et al, 2022; Ioniță et al, 2019; Ishaq, 2016; Qazi et al, 2015; Vanzella et al, 2012) and three articles analyzed the tail suspension test (Divyajyothi et al, 2015; Emon et al, 2022; Vanzella et al, 2012). Regarding temporality, only Ioniță et al (2019), Mombeini et al (2017), Zhang et al (2016), and Rabbani et al (2011) conducted chronic trials of flower extracts effects. Mombeini et al (2017) reported that, in repeated trials, tolerance to the anxiolytic effect was generated at high doses.…”
Section: Resultsmentioning
confidence: 99%
“…produced an increase in the number of crossings.Of the articles in the review, only 6 of 24 performed the LDB test to measure anxiolytic activity. All of them concluded that the extracts had anxiolytic activity compared to the vehicle, and onlyRabbani et al (2011) stated that one of the extracts was not statistically comparable to diazepam; however, no author made a statistical comparison of the extracts versus diazepam that could conclude that they had a similar effect.…”
mentioning
confidence: 99%